The biology of normal bone remodelling - Katsimbri, P. (European journal of cancer care, 2017)
During life, bone undergoes modelling and remodelling in order to grow or change shape. Bone modelling is the process by which bones change shape or size in response to physiologic influences or mechanical forces that are encountered by the skeleton, while bone remodelling takes place so that bone may maintain its strength and mineral homeostasis. During early childhood, both bone modelling (the formation and shaping of bone) and bone remodelling (the replacement or renewal of old bone) occur. The predominant process in childhood is bone modelling, while in adulthood bone remodelling predominates. The exception to this is after a fracture when we see massive increases in bone formation. During childhood and adolescence growth occurs in the bones longitudinally and radially, while in the growth plates it occurs longitudinally, thus promoting growth in size. Cartilage first proliferates in the epiphyseal and metaphyseal areas of long bones before undergoing mineralisation to form new bone.